Opencast production mesh design with Python implementation (SCIÉNDO INGENIUM, 2024)
The objective of the research was to make a production mesh in open-pit mining with Python to determine the total number of holes, mesh burden and load factor. An experimental methodology was used with an applied scope. An exploratory data analysis (EDA) was carried out, where different parameters were considered: well diameter, explosive density, bank height, rock density, among others; A review of case studies (base case) was also conducted. The study used the Pearse-Borquez method. In Python, the production mesh of 80 meters in length and 30 meters in width was built, with an incorporation of 60 holes, adding up to a total of 684 drilled holes, it was possible to determine a burden of 7 meters and a drill loaded with a block of 6 meters. It has a load factor of 0.38 kilograms of dynamite per ton to achieve adequate fragmentation, allowing us to explore the variability of results under different geological conditions and evaluate the efficiency of different types of explosives to maximize rock fragmentation.
Keywords: Python; drilling; explosive; production mesh